Contemporary crisis and renewal of public action: towards the emergence of a new form of regulation - Crise contemporaine et renouveau de l'action publique : vers l'émegence d'un nouveau mode de régulation ? (Frankfurt am Main, 2011)
"Is the major crisis that began in 2008 nearing the end? Governments and analysts have time and again announced that. Yet this diagnosis remains very premature even now. The level of unemployment is still high in many countries. While the massive aids provided by the States to the economy have allowed them to avoid the collapse of the economic system, they have paradoxically exposed the States to their own failure. Many countries in Europe are in precarious situations. Far beyond Europe the role played by the State is in question. Which measures must be taken by the public authorities in order to remedy the economic crisis? Are we witnessing the emergence of a new form of regulation? How will the general interest be carried and defended in future? How have the relations between the State and citizens changed? What are the national or continental variations on these themes? Through international comparisons, specialists from Europe, Africa and the Americas linked to CIRIEC International bring new answers to these important questions.